Розробка та дослідження можливостей системи аналізу програмних продуктів клієнтів для їх міграції до хмарних сервісів - Мірошниченко, А. А. (ХНУРЕ, 2023)
The abstract is devoted to the development and research of the capabilities of software products analysis system for their migration to cloud services. It emphasizes the growing importance of cloud migration in today’s digital era and the demand for effective tools to optimize and simplify this process. Explores the design and functionality of the proposed analysis system, which evaluates provided software products, identifies potential challenges, and offers recommendations for migration to suitable cloud platforms. The abstract delves into the software implementation, leveraging algorithms and programming languages to develop a reliable and accurate tool, as well as highlights the significance of developing such a system to optimize the migration process, minimize potential risks, and ensure compatibility with chosen cloud services.